“The Animal” After Derrida: Interrogating the Bioethics of Geno-Cide - Swazo, Norman (Les ateliers de l'éthique / The Ethics Forum, 2013)
Bioethics tends to be dominated by discourses concerned with the ethical dimension of medical practice, the organization of medical care, and the integrity of biomedical research involving human subjects and animal testing. Jacques Derrida has explored the fundamental question of the “limit” that identifies and differentiates the human animal from the nonhuman animal. However, to date his work has not received any reception in the field of biomedical ethics. In this paper, I examine what Derrida’s thought about this limit might mean for the use/misuse/abuse of animals in contemporary biomedical research. For this, I review Derrida’s analysis and examine what it implies for scientific responsibility, introducing what I have coined the “Incompleteness Theorem of Bioethics.”